Pengaruh Pengerolan Pelat Kondisi Dingin Terhadap Kekakuan Pelat Pada Bak Mobil Pick Up - Darensyah, Marcel; Sukanto, Sukanto; Erwanto, Erwanto (Jurnal Inovasi Teknologi Terapan, 2023)
A pick-up car is a car that has a tub at the back that is useful for lifting goods. The body or tailgate of the car is designed to use iron plates so that the car is stronger and more durable. Vehicles are greatly affected by noise and vibration levels. The resulting vibrations come from the engine, the floor of the vehicle cabin, and the road that has an effect on the vehicle. Vibration can be reduced by increasing the stiffness. Stiffness can be increased by making grooves in the panels. The purpose of this research is to increase the natural frequency and stiffness of the plates by forming grooves in the plates. The materials used in this study were galvanic plates with plate thicknesses of 0.6 mm and 0.8 mm. The research method is demonstrated as follows: determine the dimensions of the plate, the process of making grooves, measure and analyze the natural frequency and stiffness. The length and width of the plates are 580 mm and 600 mm. The groove used is in the form of a trapezoid by means of a rolling process. The results of the grooved plate experienced a 3-fold increase in frequency compared to the flat plate.